2018
DOI: 10.1021/acs.organomet.8b00678
|View full text |Cite
|
Sign up to set email alerts
|

Alkyne [2 + 2 + 2] Cyclotrimerization Catalyzed by a Low-Valent Titanium Reagent Derived from CpTiX3 (X = Cl, O-i-Pr), Me3SiCl, and Mg or Zn

Abstract: Inter-, partially intra-, and intramolecular [2 + 2 + 2] cycloadditions of alkynes were catalyzed by a low-valent titanium species generated in situ from the reduction of CpTi(O-i-Pr) 3 , CpTiCl 3 , or Cp*TiCl 3 with Mg or Zn powder in the presence of Me 3 SiCl. The role of Me 3 SiCl as an additive in the reaction mechanism is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 118 publications
1
19
1
Order By: Relevance
“…By comparison, the use of monocyclopentadienyltitanium­(III) halides [Ti­(η 5 -C 5 R 5 )­X 2 ] in organic synthesis has remained almost unexplored, although these derivatives have been known for decades . Nevertheless, half-sandwich titanium­(III) species are receiving increasing attention as catalyst in organic synthesis . In particular, [Ti­(η 5 -C 5 Me 5 )­Cl 2 ] has been recently proposed as the active species in several radical processes, although the aggregated structure of this compound remains unknown in the literature .…”
Section: Introductionmentioning
confidence: 99%
“…By comparison, the use of monocyclopentadienyltitanium­(III) halides [Ti­(η 5 -C 5 R 5 )­X 2 ] in organic synthesis has remained almost unexplored, although these derivatives have been known for decades . Nevertheless, half-sandwich titanium­(III) species are receiving increasing attention as catalyst in organic synthesis . In particular, [Ti­(η 5 -C 5 Me 5 )­Cl 2 ] has been recently proposed as the active species in several radical processes, although the aggregated structure of this compound remains unknown in the literature .…”
Section: Introductionmentioning
confidence: 99%
“…Reactions performed at lower temperatures (80 or 100 °C) afforded no naphthalene product; however, evolution of stoichiometric amounts of benzene signaled that β-hydrogen abstraction of Cp* 2 ZrPh 2 did occur. Moreover, low-valent Ti is competent for trimerization under mild conditions . Thus, the high reaction temperature may be more readily associated with the barrier for the generation of an active Ti II species.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, low-valent Ti is competent for trimerization under mild conditions. 39 Thus, the high reaction temperature may be more readily associated with the barrier for the generation of an active Ti II species. Notably, 2 is furnished in good yield at 1 mol % catalyst loading, while similar reactions employing Ni or Pd catalysts require 10 mol % catalyst loading to achieve comparable yields.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In 2017, Okamoto and co-workers demonstrated that low-valent titanium species catalyzed the [2+2+2] cycloadditions of alkynes using CpTi(Oi-Pr) 3 , CpTiCl 3 , or Ti(Oi-Pr) 4 combined with Mg or Zn powder as metal reductant in the presence of Me 3 SiCl that played a crucial role for the cycloaddition to proceed (Scheme 2). 62 Inter-, partially intra-, and intramolecular alkyne cyclotrimerization can be accomplished in THF (0.5 M) at 40-45 °C for 12-20 h. Under these optimized reaction conditions, the corresponding 1,3,5-and 1,2,4-trisubstituted benzenes were obtained as a mixture of regioisomers (up to 41:59) in 16-85% yield.…”
Section: Cyclotrimerization Of Alkynesmentioning
confidence: 99%